A "turn-on" fluorescent probe used for the specific recognition of intracellular GSH and its application in bioimaging. Issue 20 (9th February 2016) - Pang, Lanfang; Zhou, Yanmei; Wang, Enze; Yu, Fang; Zhou, Hua; Gao, Wenli
Abstract : A "turn-on" fluorescent probe used to specifically recognize intracellular GSH and its application in bioimaging. Abstract : We have designed and synthesized a carbazole-based fluorescent probe (CZ-Nm) for the specific recognition of GSH over Cys and Hcy. The probe is almost non-fluorescent owing to the photoinduced electron transfer (PET) process from the carbazole fluorophore to the nitroolefin moiety. Upon treatment with GSH, owing to the Michael addition of GSH to the double bond of the nitroolefin moiety, the probe shows a fluorescence enhancement and absorption change. The CZ-Nm probe displays desirable properties such as acting as a "naked eye" probe, a wide linear range of 0–0.01 M, high sensitivity, and strong anti-jamming capability. More importantly, the probe can also be successfully applied to the detection of intracellular GSH with a bright fluorescence signal, good cell permeability and bio-compatibility.